Battling the Prince : a Woman Fights for Democracy. - Snyder-Hall, Claire (SUNY series in new political science., 2021)
"What happens when a democratic theory professor gets involved with the Democratic Party? In this political memoir, Claire Snyder-Hall shares lessons learned from eight years in party politics. She tells the story of organizing a grassroots campaign for state senate in a district dominated by good ole boys, of a political milieu in which a letter to the editor results in a smear campaign and broken friendships, and of battling a party establishment more concerned about shoring up its own power than engaging everyday people or fighting for their needs. Using an intersectional understanding of identity, Snyder-Hall unpacks the ways in which gender, class, and sexuality affect political campaigns, and offers advice for progressives. She also draws on insights from Machiavelli, Rousseau, Marx, and Gramsci to argue that a democratic republic requires a politically engaged populace, a democratic culture, and economic justice, and this can only be achieved when people defend democratic values in the face of rising authoritarianism, stand up to bullies, transform their political consciousness, and a create a party willing to fight for the 99%." --